# Order of Operations confused

• Sep 1st 2010, 09:27 PM
tomtomgreg
Order of Operations confused
So i was working through my math book and i got to some questions about Order of Operations or BEDMAS (brackets, exponents, division, multiplication, adding, subtracting)

now im used to doing it but not with variables included i tried to figure it out but i just have no idea.

the questions are

2(x + 3)(x + 4) =

also when there is an exponent included

3(x + 3)^2 =

any help would be appreciated
• Sep 1st 2010, 09:32 PM
undefined
Quote:

Originally Posted by tomtomgreg
So i was working through my math book and i got to some questions about Order of Operations or BEDMAS (brackets, exponents, division, multiplication, adding, subtracting)

now im used to doing it but not with variables included i tried to figure it out but i just have no idea.

the questions are

2(x + 3)(x + 4) =

also when there is an exponent included

3(x + 3)^2 =

any help would be appreciated

(a+b)(c+d) = ac+ad+bc+bd nothing new here right?
• Sep 1st 2010, 09:34 PM
Educated
2(x + 3)(x + 4) = ?

First you substitute whatever x is, then you work out the number inside the brackets(brackets first). Then you multiply them together(multiplication after).

3(x + 3)^2 = ?

First you substitute whatever x is into the equation, then you solve the brackets, then do to the power of 2, then multiply by 3.
• Sep 1st 2010, 09:38 PM
tomtomgreg
Quote:

Originally Posted by Educated
2(x + 3)(x + 4) = ?

First you substitute whatever x is, then you work out the number inside the brackets(brackets first). Then you multiply them together(multiplication after).

3(x + 3)^2 = ?

First you substitute whatever x is into the equation, then you solve the brackets, then do to the power of 2, then multiply by 3.

for example on the second question i have the answer key but i can't figure out how to run the operation.
The work book doesn't state what the variable is.

the answer to 3(x + 3)^2 = (according to my work book is) 3x^2 + 18x + 27

i don't even know how it got that...
• Sep 1st 2010, 09:44 PM
Educated
That is called expanding the brackets.

You can use the FOIL method to expand it:

First - multiply the first value in the first bracket by the first value in the second bracket
Outer - multiply the first value in the first bracket by the last value in the second bracket
Inner - multiply the last value in the first bracket by the first value in the second bracket
Last - multiply the last value in the first bracket by the last value in the second bracket
Then multiply everything by whatever is outside of the brackets.

If you do not understand it, look up expanding brackets.
• Sep 1st 2010, 09:46 PM
undefined
Quote:

Originally Posted by tomtomgreg
for example on the second question i have the answer key but i can't figure out how to run the operation.
The work book doesn't state what the variable is.

the answer to 3(x + 3)^2 = (according to my work book is) 3x^2 + 18x + 27

i don't even know how it got that...

3(x+3)^2 = 3(x^2+6x+9) = 3x^2+18x+27

If you haven't been taught that (x+3)^2 = x^2+6x+9 then the question should not have been given to you in the first place.
• Sep 1st 2010, 09:51 PM
tomtomgreg
so would i run it like

= 3(x + 3)^2
= 3(x + 3)(x + 3)
= 3 (x^x) (x^3) (3^x) (3^3)
= 3 (x^2) (3x) (3x) (9)
= 3 x^2 6x 9
= 3x^2 + 18x + 27
• Sep 1st 2010, 09:54 PM
tomtomgreg
Quote:

Originally Posted by undefined
3(x+3)^2 = 3(x^2+6x+9) = 3x^2+18x+27

If you haven't been taught that (x+3)^2 = x^2+6x+9 then the question should not have been given to you in the first place.

well in my work book i was working on polynomials and then these questions came up and i guess i didn't make the connection to using FOIL, thanks for the help though
• Sep 1st 2010, 09:55 PM
undefined
Quote:

Originally Posted by tomtomgreg
so would i run it like

= 3(x + 3)^2
= 3(x + 3)(x + 3)
= 3 (x^x) (x^3) (3^x) (3^3)
= 3 (x^2) (3x) (3x) (9)
= 3 x^2 6x 9
= 3x^2 + 18x + 27

This line

= 3 (x^x) (x^3) (3^x) (3^3)